Investigation of Minimization of Excess Sludge Production in Sequencing Batch Reactor by Heating Some Sludge - Pazoki, Maryam; Takdastan, Afshin; Jaafarzadeh, Nematollah (Asian Journal of Chemistry, 2010)
The ultimate disposal of excess sludge generated from activated sludge processes is one of the most challenging problems for wastewater treatment. Most biological wastewater treatment processes are temperature sensitive and thus increasing process temperature is effective for reducing sludge production. In this research, Two sequencing batch reactor (SBR) reactors with of 20 L being controlled by on-line system are used. Long term (8 months) continuous experiments were conducted to identify the effect of controlled temperature up-shifting within 30 to 70 ºC for 1 h in part of sludge to reduction of biological excess sludge. After providing the steady state in the reactors, sampling and testing parameters such as COD, MLSS, MLVSS, DO, SOUR, SVI and Y coefficient were done. Overall, temperature shift to 60 ºC for 1 h shows during the solid retention time of 10 days, the kinetic yield coefficient decreases from 0.63 to 0.33. In other words reduces excess sludge up to 47 %. However the soluble COD increased slightly in the effluent and the removal percentage decreased from 89 in the control reactor to 57 in the test reactor; while the amount of SVI and SOUR in this temperature reduced to 45 mL/g and 9 mg O2/h.gVSS, respectively. In temperature of 70 ºC no sludge was seen but effluent SCOD and turbidity was increased. It also did not meet the wastewater disposal standard and the wastewater had a bad adore.